The Land Rights of Indigenous Peoples: Revaluation of Papua Special Autonomy - Pelupessy, Eddy (Hasanuddin Law Review, 2017)
The purpose of Special Autonomy for Papua is to resolve the source of the problem in Papua, especially concerning the rights of indigenous peoples. Normatively, the background of local autonomy for Papua is affirmed in Act No. 21 of 2001 on Papua Special Autonomy. The results shows that the recognition and protection of the land rights of indigenous peoples have been set clearly in the national legal system, such as Agrarian Law, Forest Law, as well as in Mineral and Coal Mining Law. However, recognition and protection of indigenous peoples’ rights to land in various legal products is still ambivalent. The essence of protection of indigenous peoples’ rights to land is also clearly regulated in Act No. 21 of 2001 and Perdasus No. 23 of 2008 has put customary law community on ownership of communal land is not the object of development, especially in the field of investment. The customary right and indigenous land which is the property and become an authority on indigenous peoples must be recognized by the government and regional and national communities about its presence. Therefore, the government should strive to protect the customary right through regulation of the Ministry of Agrarian and Land Agency and other laws related to the issue of customary rights, customary lands, indigenous peoples and their authority.